The Relationship Of Infectional Diseases To The Nutritional Status Of Toddlers During The Covid-19 Pandemic - Rini Dwi Mulyani; Nuril Nikmawati; Riska Ismawati Hakim; Fatma Hidayah (Midwifery and Nursing Research, 2022)
Backgroud: The COVID-19 pandemic has had a significant impact on the health system and the economy. Children under the age of 5 are very vulnerable to infectious diseases such as malaria, pneumonia, diarrhea, HIV and tuberculosis. The results of the 2018 Basic health research in Indonesia that the prevalence of underweight/bad nutrition problems was 17.7%, and stunting reached 30.8%. Methods: This type of research is an analytic study and the design of this research is cross sectional. The sampling technique in this study used simple random sampling with inclusion criteria in this study were children aged 0-60 months who visited at the Magelang Community health center complete nutritional status data recorded, namely weight, age, medical diagnosis in the patient's medical record. The sample size is 220 determined by the slovin formula. Result: The majority of respondents are children under five with a diagnosis of infectious lung disease of 179 (81.4%). The nutritional status of the majority of respondents are toddlers with good nutritional status of 164 (74.5%). The results of the analysis showed that there was a relationship between pulmonary infection and nutritional status of children under five at the Magelang Community health center, with a Z value of 11,432a with a significance value of 0.003 (< 0.05). Conclusion: There is a relationship between infection diseases and nutritional status of children under five at the Magelang Community health center. It is important for mothers to ensure that children are raised with good parenting and nutrition patterns, implement health protocols so that children are protected from infectious diseases that will have an impact on poor nutritional status.